2019
DOI: 10.1057/s41285-019-00127-8
|View full text |Cite
|
Sign up to set email alerts
|

Responsibility in dealing with genetic risk information

Abstract: Predictive testing information raises questions about risk communication, health responsibility, and about how to deal with the gap between knowledge of risks and options to act on this knowledge. For some diseases identified by predictive testing, specific treatments or interventions are available, while other diseases, thus far, remain untreatable or unpreventable; this triggers different forms of responsibility. Gender also often intersects with moral responsibility, regarding risk communication but also re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…Factors suggested to influence an individual's decision to engage in predictive testing across all diseases included perceived severity of the illness, treatability, family history, age, health attitudes, upbringing and the presence of co-morbidities. Results for BC and AD aligned with those of a similar study in Germany [25]. However predictive testing was more often perceived in a positive light for BC and AD than for RA in the present study.…”
Section: Summary Of Findingssupporting
confidence: 89%
See 2 more Smart Citations
“…Factors suggested to influence an individual's decision to engage in predictive testing across all diseases included perceived severity of the illness, treatability, family history, age, health attitudes, upbringing and the presence of co-morbidities. Results for BC and AD aligned with those of a similar study in Germany [25]. However predictive testing was more often perceived in a positive light for BC and AD than for RA in the present study.…”
Section: Summary Of Findingssupporting
confidence: 89%
“…This study was a qualitative study, with an inductive approach, using focus groups following a structured discussion guide incorporating case vignettes [ 23 ]. Focus group with members of the general public were conducted at the Medical School of the University of Birmingham, United Kingdom (UK) between September and October 2017, as part of an international multi-centre comparative study of public perceptions of recent developments in genetic testing [ 24 , 25 ]. Ethical approval was granted by the University of Birmingham Science, Technology, Engineering and Mathematics Ethical Review Committee (ERN_17-0298).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A German study showed that lay people perceive risk information as highly normatively charged, and often as an emotionally significant threat . It would therefore seem to be necessary to provide lay people with a deeper understanding of risk information and of the limitations of genetic knowledge with respect to one's own health responsibility (Wöhlke and Perry, 2019). Similar results were found for lay people in Italy, who perceived genetic testing to be very helpful for disease prevention but were simultaneously afraid that a positive result, the detection of a genetic variant, could affect their life planning and leave them without the ability to act to address the risk (Oliveri et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…Four vignettes were also used in the focus groups, which, since they were developed in cooperation with another research project, also included other topics (i.e., direct-to-consumer genetic testing, use of biomarkers). This article focuses on the detailed analysis of the third vignette, while the others are analyzed and published elsewhere (Schaper et al, 2018 ; Wöhlke and Perry, 2019 ; Wöhlke et al, 2019 ); this selection is due to the fact that the vignettes were designed to address various ethical issues in the field of genetic and genomic information. The focused analysis took into account the general discussion process and each group dynamic.…”
Section: Methodsmentioning
confidence: 99%